2005
DOI: 10.3748/wjg.11.4364
|View full text |Cite
|
Sign up to set email alerts
|

Blood micronutrient, oxidative stress, and viral load in patients with chronic hepatitis C

Abstract: Abstract Abstract Abstract AIM:To assess the extent of micronutrient and oxidative stress in blood and to examine their linkages with viral loads in chronic hepatitis C patients. METHODS:Hepatitis C virus (HCV)-RNA levels were quantified in the serum from 37 previously untreated patients with chronic hepatitis C. The plasma and erythrocyte micronutrients (zinc, selenium, copper, and iron) were estimated, and malondialdehyde (MDA) contents were determined as a marker to detect oxidative stress. Antioxidant enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 27 publications
4
47
2
Order By: Relevance
“…Hence, comparison of our results of NO and Cu measurements in the blood of CVHC patients with the findings of other studies, in which NO and Cu were measured by other than EPR methodological approaches [1,[3][4][5][6], showed their coincidence: the levels of NO and CU in whole blood of CVHC patients was increased significantly in comparison with the normal level. This suggests the use of quantitative EPR analysis for direct measurements of nitroxide and copper in biological substrates.…”
Section: Resultssupporting
confidence: 59%
“…Hence, comparison of our results of NO and Cu measurements in the blood of CVHC patients with the findings of other studies, in which NO and Cu were measured by other than EPR methodological approaches [1,[3][4][5][6], showed their coincidence: the levels of NO and CU in whole blood of CVHC patients was increased significantly in comparison with the normal level. This suggests the use of quantitative EPR analysis for direct measurements of nitroxide and copper in biological substrates.…”
Section: Resultssupporting
confidence: 59%
“…Hence, demographic factors such as gender and lifestyle could be adjusted. (2) The ROS production by neutrophils was measured without a phagocytic stimulus, and hence our results revealed the relationship between Se concentration and neutrophil-derived oxidative stress. (3) We investigated not only the neutrophil ROS production but also the other 2 functions of PA and SOA simultaneously.…”
Section: Introductionmentioning
confidence: 95%
“…Se refers to relative factors of oxidative stress associated with diseases such as cancer, infectious disease, and heart disease [1][2][3][4][5]. Se is contained in the active center of enzymes that reduce the reactive oxygen species (ROS), such as glutathione peroxidase (GSH-Px), which has been reported to have an anti-oxidative effect and prevent cancer [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The study of Fischer showed that the liver contains a high concentration of Se, which participates in many biological processes that range from cellular antioxidant defense to the protection and repair of DNA to apoptosis (Fischer et al 2006). Se deficiency could induce liver necrosis in rats (Matsuda et al 1998), hepatosis dietetica in pigs (Doyle et al 2011), oxidative damage in the livers of patients with HCV-related CLD (Ko et al 2005) and apoptosis in rat livers (Miao et al 2013). …”
Section: Introductionmentioning
confidence: 98%